The chameleon effect in customer relationship management: Experiments on the spillover effects of mimicry in natural settings of a chain hotel and a chain grocery shop - Kulesza, Wojciech; Dolinski, Dariusz; Muniak, Paweł; Borkowska, Joanna; Bibikova, Polina; Grzyb, Tomasz (Frontiers in Psychology, 2023)
Numerous experiments have proven that mimicry is highly beneficial (mainly to the mimicker but also to the mimickee). Some studies have shown initial data suggesting the potential of applying this knowledge to business settings. In the present paper we unpack this issue in two ways. First, by presenting potential benefits stemming from mimicry for the mimicking dyad, and second for the business environment represented by the mimicker. Two consecutive studies: a Pretest and a Main Experiment run in natural settings showed great potential in improving the assessments of quality of service provided by verbally mimicking (or not). The results of both studies showed that mimicry offers benefits for the mimicker (increased employee kindness and employee evaluation), and also spillover to the organization/company represented by the mimicking employee (increased opinion of and willingness to return to the shop/hotel). Future research directions and limitations are discussed.